Transcription factor-mediated gene regulatory networks contributes to reproductive stage drought tolerance in rice (Oryza sativa) - KAUR, SIMARDEEP; SEEM, KARISHMA; S, TAMIL SELVAN; MISHRA, DWIJESH CHANDRA; KAUNDAL, RAKESH; KUMAR, SURESH; MOHAPATRA, TRILOCHAN (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during rainy (kharif) seasons of 2020–22 at ICAR-Indian Agricultural Research Institute, New Delhi, to examine transcription factors (TFs) in drought tolerance using two rice (Oryza sativa L.) cultivars, drought-tolerant Nagina-22 and drought-sensitive IR-64. Immature panicles were used to prepare transcriptome libraries, sequenced with Paired-End 150 bp chemistry for both control and drought-treated samples. Bioinformatic analysis of the data using TFs extracted from PlantTF database revealed that majority (335) of the TFs were up-regulated in Nagina-22, while 92 were down-regulated under stress. Conversely, a significant number of TFs (359) were down-regulated in IR-64 under stress. Gene ontology and gene regulatory network analyses of the differentially expressed TFs indicated that several crucial biological processes and molecular functions were enriched with higher number of up-regulated TFs in Nagina-22 under stress. Significantly up-regulated expression of TFs, particularly WRKY, ERF, MYB, NAC, and bHLH, in panicle of N-22 must be responsible for terminal drought tolerance. Our findings confirm the master-regulator role of TFs in gene-regulatory networks essential for tolerance to complex trait like drought. The information might be valuable in selecting potential candidate parental lines for drought tolerance breeding and genetic manipulation of rice cultivars towards the development of climate-resilient cultivars.